2012
DOI: 10.1136/jmedgenet-2012-100819
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of exome sequencing in undiagnosed genetic conditions

Abstract: BackgroundThere is considerable interest in the use of next-generation sequencing to help diagnose unidentified genetic conditions, but it is difficult to predict the success rate in a clinical setting that includes patients with a broad range of phenotypic presentations.MethodsThe authors present a pilot programme of whole-exome sequencing on 12 patients with unexplained and apparent genetic conditions, along with their unaffected parents. Unlike many previous studies, the authors did not seek patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
344
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(372 citation statements)
references
References 54 publications
12
344
1
5
Order By: Relevance
“…8 In fact, a much higher rate of ~50% was seen in a different pilot study in which more stringent predetermined criteria were applied for selecting patients suitable for ES. 9 From an Review economic perspective, a recent study has shown that, compared with multiple single-gene or low-throughput testing, ES has the potential to provide a significant cost benefit for patients who remain undiagnosed after a few traditional approaches. 2 ES has shown success most often in cases in which it does not rely on a priori knowledge of the genetic condition.…”
Section: Exome Sequencingmentioning
confidence: 99%
“…8 In fact, a much higher rate of ~50% was seen in a different pilot study in which more stringent predetermined criteria were applied for selecting patients suitable for ES. 9 From an Review economic perspective, a recent study has shown that, compared with multiple single-gene or low-throughput testing, ES has the potential to provide a significant cost benefit for patients who remain undiagnosed after a few traditional approaches. 2 ES has shown success most often in cases in which it does not rely on a priori knowledge of the genetic condition.…”
Section: Exome Sequencingmentioning
confidence: 99%
“…That being said, parents can offer observations and ideas, and we can push for solutions. Nineteen months after the initial report by Need et al, 2 five viable approaches to treatment are under active consideration, thanks to relentless digging by afflicted families. One parent found a compound that seems to have measurably raised the quality of life in one NGLY1 child.…”
Section: © American College Of Medical Genetics and Genomicsmentioning
confidence: 99%
“…Two new developments in genetics promise to dramatically shorten the time to reach a successful diagnosis: next-generation sequencing (NGS) and family engagement through social media. The very speed with which Need et al 2 and Enns et al 1 were published suggests a new model for clinicians and researchers. In this model, families, patients, and scientists work jointly to find new patients, confirm or refute hypotheses, exchange clinical information, enhance collaboration methods, and support research toward understanding and treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients diagnosed through research and clinical exome sequencing has increased exponentially since the inception of the technology in 2008 and the introduction of the clinical test in 2011 (NIH Health Consensus Conference Statement, 2001;Worthey et al 2011;Dixon-Salazar et al 2012;Need et al 2012;Sailer et al 2012;Hanchard et al 2013;Shamseldin et al 2013). Exome sequencing has been instrumental in discovering the pathogenic etiology in patients in whom traditional molecular methods were uninformative and is uniquely useful in overcoming limitations posed by traditional molecular diagnostic strategies in the identification of oligogenic findings.…”
Section: Introductionmentioning
confidence: 99%